(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Objective: to make a comparative assessment of the risk of unfavorable outcome after percutaneous coronary interventions in patients with coronary heart disease with concomitant chronic obstructive pulmonary disease to determine the possibilities of drug correction. Materials and methods: Results of PCI of 726 patients with IHD made the basis of the work: group I consisted of 106 patients who underwent PCI with COPD; group II included 620 patients after PCI without COPD. Results: The presence of concomitant COPD is associated with an increased risk of hospital mortality and the development of cardiovascular complications (CVC) during the observation period after PCI. Thus, patients with COPD were statistically significantly older, female prevailed, and a more severe course was determined (Killip III, in 15.1% versus 4.1% in group II; p <0.05); predominantly 3 vascular lesions (in 60.4% versus 21.0%; p <0.05); the risk of hospital mortality (3.8% versus 0.02%; p <0.05) is higher. Arterial hypertension, smoking, dyslipidemia, and decreased glomerular filtration rate (all p <0.05) are more often diagnosed among patients with COPD as a risk factor for CVC. Regression analysis showed that the risk of unfavorable events directly correlated with age (r = 0.72), Charlson comorbidity index (r = 0.63), risk group (r = 0.58) and the frequency of COPD exacerbations (r = 0.50). Conclusions: A comparative study of CVC results showed that in IHD patients with concomitant COPD there are significant correlations of unfavorable PCI outcome (mortality, repeated revascularization, and myocardial infarction) with the main clinical characteristics of patients with COPD (CAT, mMRC, frequency of COPD exacerbations) and comorbidity index. Damage to the cardiovascular and respiratory systems forms a vicious circle of mutual complications with the need for a comprehensive examination of the patient and the formation of a high-risk group in order to optimize drug correction.